Optical Disc for Long-Term Data Storage Based on Chromium Film - Gorbov, I.V.; Manko, D.Yu.; Kryuchyn, A.A.; Zichun Le; Minglei Fu; Pankratova, A.V. (Металлофизика и новейшие технологии, 2016)
The applicability of the Ag, Au, Al, and Cr films as the reflective layer of optical discs for long-term data storage is investigated. Thin metal films are obtained on glass substrate by the method of vacuum thermal deposition. Their adhesive properties are revealed. As shown, a chromium film is characterized by the best adhesion to the glass substrate among all investigated ones. Optical disc for long-term storage is proposed. The information on disk is recorded directly on the reflective metal film. The information on the positive photoresist layer is recorded according to already existed CD standard using laser-burning station. Then, the mask for following chemical etching of chromium film is created. Analysis of morphology of recorded pits proves suitability of the long-term data storage disc to existing standards. Chromium optical disc created in this way is successfully read in a standard DVD player.